2015
DOI: 10.1088/1748-6041/10/2/025002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different methods for effective introduction of platelet-rich plasma on PLGA woven mesh

Abstract: For successful tissue regeneration, effective cell delivery to defect site is very important. Various types of polymer biomaterials have been developed and applied for effective cell delivery. PLGA (poly lactic-co-glycolic acid), a synthetic polymer, is a commercially available and FDA approved material. Platelet-rich plasma (PRP) is an autologous growth factor cocktail containing various growth factors including PDGF, TGFβ-1 and BMPs, and has shown positive effects on cell behaviors. We hypothesized that PRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Fourier transform infrared (FTIR) spectroscopy analysis of nanofiber samples ( Figure 3 a) showed the presence of a broad band at 3100–3150 cm −1 , which can be attributed to O–H stretching vibrations of the phenyl hydroxyl groups present in the EGCG . Furthermore, a small peak at 1600 cm −1 corresponding to the C=C bond present in the EGCG structure also appeared, confirming successful coating of EGCG on the nanofiber surface.…”
Section: Resultsmentioning
confidence: 89%
“…Fourier transform infrared (FTIR) spectroscopy analysis of nanofiber samples ( Figure 3 a) showed the presence of a broad band at 3100–3150 cm −1 , which can be attributed to O–H stretching vibrations of the phenyl hydroxyl groups present in the EGCG . Furthermore, a small peak at 1600 cm −1 corresponding to the C=C bond present in the EGCG structure also appeared, confirming successful coating of EGCG on the nanofiber surface.…”
Section: Resultsmentioning
confidence: 89%
“…A number of studies showed that PRP could improve tendon cell proliferation and matrix synthesis in vitro, 52 augment tendon healing in vivo, 8 and improve cell-material interaction. 23 According to a previous study on rabbit PRP, 9 the mean number of platelets in whole blood was (259.06 ± 88.04) × 10 3 /µL, and that in PRP was (924.77 ± 330.86) × 10 3 /µL. In addition, the mean number of leukocytes in whole blood was (6.18 ± 2.01) × 10 3 /µL, and that in PRP was much decreased, with (0.06 ± 0.09) × 10 3 /µL.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that treatment of PRP with CaCl 2 enables platelet activation leading to fibrin network formation [41]. First, activated and inactivated platelets were analyzed on coverslips since our grafts consist of fiber structure and to distinguish fibrin network can be difficult.…”
Section: Prp Applicationmentioning
confidence: 99%